Thermoacoustic Stability Boundaries in the Model Combustion Chamber with a Gas-Centered Swirl Coaxial Injector. (19th November 2019) - Min, Yong Ho; Sohn, Chae Hoon; Yoon, Youngbin
Abstract : The stability of a combustion chamber with a gas-centered swirl coaxial injector is investigated over a wide range of operating conditions in the aspect of thermoacoustic instabilities. First, flame shapes induced by the injector are analyzed for various recess lengths from experimental results. The spreading angle and flame size are reduced as the recess length increases. And, as a stability criterion, the damping factor is introduced. The operating conditions are divided into 7 sets with 9 tests, and fuel mass flow is fixed in each set. Stability boundaries are identified in terms of damping factor for the 63 tests by experiments without external perturbations. The stability map for the self-excited instability is obtained and it reveals two unstable regions. One is located at low dynamic head ratio and the other one is at high dynamic head ratio. A stable region is found at moderate dynamic head ratios. Relative stability is evaluated by various flow parameters over a wide range of operating conditions in the combustion chamber with a gas-centered swirl coaxial injector.